OPTIMALISASI PENGUATAN NILAI-NILAI MODERASI BERAGAMA MELALUI AKSI GOTONG ROYONG MENYAMBUT HUT RI KE 79 DI DESA TARUSAN DANUM - Ajahari, Ajahari; Sihung, Sihung; Yusup, Wirastiani Binti; Yalla, Elisabeth; Anggara, Danda; Nisapingka, Diren; Angeli, Monica; Yuverdina, Yuverdina; Pernando, Jhony; Rifa’i, Ibnu; Syahrani, Septya Dwi; Rahmawati, Annisa Awallia; Rozi, Ahmat Fahrul; Fitrila, Najima (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
KKN Nusantara Religious Moderation is a priority program of the Ministry of Religion of the Republic of Indonesia which was initiated through collaboration with various universities in Indonesia, in order to maximize the value of tolerance in society. KKN Nusantara Religious Moderation in 2024 was implemented in Central Kalimantan, precisely in Katingan Regency, by sending 12 groups to different villages with programs that could foster an attitude of tolerance in society. The purpose of KKN NMB is to build a commitment to community understanding related to the values ​​of religious moderation within the framework of Bhineka Tunggal Ika. The KKN NMB community service method uses the PAR Participatory Action Research type or community participation action research in Tewang Rangkang Village. The results of the NMB KKN activities show that the strengthening of the values ​​of religious moderation in the Tarusan Danum Village community on a scale of change is slightly better than before the arrival of the NMB KKN, especially through mutual cooperation actions to enliven the 79th Anniversary of the Republic of Indonesia. As for community participation towards being pro-active again with a commitment in each respective place of worship (Islam, Christianity and Hinduism) willing to carry out and implement the values ​​of religious moderation. Thus, the realization of the priority program of the Ministry of Religion together with PTK Nusantara is able to have a massive and sustainable impact on society